Growing stories from India: religion and the fate of agriculture - Sanford, A. Whitney (Culture of the land, 2012)
The ecological imagination: from paradigm to practice -- Narratives of agriculture: how did we get here? -- Balaram and the Yamuna River: entitlement and presumptions of control -- Borrowing Balaram: alternative narratives -- The festival of Holi: celebrating agricultural and social health -- The land in between: constructing nature, wilderness, and agriculture -- Restoration, reciprocity, and repair: revising the ecological imagination